Human Capital Efficiency and Employee Productivity: A Comparative Analysis of the Manufacturing Sector vs. Service Sector Public Listed Companies in Sri Lanka - Wanigasekara, W.A.D.K.J.; Deshika, N.P.T. (Faculty of Management Sciences, University of Sri Jayewardenepura, 2021)
Human capital is one of the most vital organizational knowledge assets, which is a part of organizational Intellectual Capital. Therefore, it contributes to organizational competitive advantage through enhancing employee productivity. Hence, the objective of this study was to find out the relationship between Human Capital Efficiency (HCE) and Employee Productivity (EP) in manufacturing sector companies and service sector companies listed in Colombo Stock Exchange as a comparative study. Value Added Intellectual Coefficient (VAIC) is a method used to measure the value creation efficiency of a company and HCE is one component of VAIC, which has a substantial impact on EP. Therefore, it is vital for finding out the relationship between HCE and EP in the practical scenario. But, there is a dearth of studies related to the relationship between HCE and EP in Sri Lanka. This study is carried out as a solution for bridging this empirical and contextual gap. Data were collected from 25 manufacturing companies and 25 service sector companies (Hotel and travel sector) during the period from 2015 to 2019. The data were analyzed using the Pearson Correlation and regression. The results of the data analysis indicated that the relationship between HCE and EP is moderate and significant in service sector companies, while an insignificant weak relationship was found in manufacturing sector companies. Further, a significant impact of HCE on EP was found in the service sector, but that impact was not significant in the manufacturing sector. It can be concluded that service sector companies pay more attention to enhance the HCE since the knowledge and skill embedded in employees are more valuable in providing services to their customers than manufacturing sector companies. Ultimately, the results show that good HCE can indeed improve EP, which has significant meanings for investors, company management, decision-makers, and industry regulators.
Keywords: Employee Productivity, Human Capital Efficiency, Manufacturing sector, Service sector